Experimental research on combined effect of obstacle and local spraying water fog on hydrogen/air premixed explosion. (5th December 2022) - Xia, Yuanchen; Zhang, Bin; Zhang, Jinnan; Wang, Boqiao; Chen, Li; Wang, Ruiqi; Bekele, Amanuel Girma; Shi, Jihao; Wu, Wanqing; Wang, Zhihao
Abstract: In order to reveal the mechanism of water fog explosion suppression and research the combined effect of water fog and obstacle on hydrogen/air deflagration, multiple sets of experiments were set up. The results show that the instability of thermal diffusion under lean combustion conditions is the main influencing factor of hydrogen/air flame surface instability, and the existence of water fog will aggravate the hydrogen/air flame surface instability. When obstacle is not considered, 8 μm, 15 μm, 30 μm water fog can significantly reduce the flame velocity and explosion overpressure of hydrogen/air, 45 μm fine water fog plays the opposite role. When considering the relative position of the water fog release position and the obstacle, the 8 μm, 15 μm, 30 μm water fog has almost no suppression effect when released near the obstacle, but a significant suppression effect occur, when using the 45 μm water fog. In the field of theoretical research, the research results not only provide an experimental basis for the fine water fog to reduce the consequences of hydrogen explosion accidents, and the optimal diameter range used by the water fog, but also provide experimental reference for the numerical simulation of hydrogen/air explosion suppression in semi-open space, and promote the development of hydrogen explosion suppression theory. In terms of engineering applications, this study can provide a theoretical basis for the layout of fire fighting equipment in the engine room of nuclear power plants or hydrogen-powered ships. Highlights: Suppression effects of water fog parameter on hydrogen-air explosion are analyzed. Deflagration characteristics of hydrogen-air are presented. Combined effects of obstacle and local water fog on explosion are presented. The results are suitable for the emergency management of hydrogen safety.